Assessing Task Migration Impact on Embedded Soft Real-Time Streaming Multimedia Applications. (22nd November 2007) - Acquaviva, Andrea; Alimonda, Andrea; Carta, Salvatore; Pittau, Michele
Abstract : Multiprocessor systems on chips (MPSoCs) are envisioned as the future of embedded platforms such as game-engines, smart-phones and palmtop computers. One of the main challenge preventing the widespread diffusion of these systems is the efficient mapping of multitask multimedia applications on processing elements. Dynamic solutions based on task migration has been recently explored to perform run-time reallocation of task to maximize performance and optimize energy consumption. Even if task migration can provide high flexibility, its overhead must be carefully evaluated when applied to soft real-time applications. In fact, these applications impose deadlines that may be missed during the migration process. In this paper we first present a middleware infrastructure supporting dynamic task allocation for NUMA architectures. Then we perform an extensive characterization of its impact on multimedia soft real-time applications using a software FM Radio benchmark.